1990
DOI: 10.2307/3430904
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Elevated Blood Lead during Pregnancy in a Population Surrounding a Lead Smelter in Kosovo, Yugoslavia

Abstract: We are prospectively examining the relation between environmental lead exposure and pregnancy outcome in cohorts of women exposed to a wide range of air lead concentrations. Titova Mitrovica, Yugoslavia, is the site of a large lead smelter, refinery, and battery factory. At midpregnancy, 602 women in T. Mitrovica and 900 women in Pristina, a non-lead-exposed control town, were interviewed. Blood was obtained for blood lead (PbB), hemoglobin, erythrocyte protoporphyrin, and serum ferritin measurements. Women we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
39
0
1

Year Published

1991
1991
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 10 publications
2
39
0
1
Order By: Relevance
“…Other clinical studies have demonstrated that high body iron stores are associated with decreased blood lead levels (Graziano et al 1990). These previous studies formed the basis of our hypothesis that the HFE gene would be a candidate gene for modifying lead absorption and body burden.…”
Section: )mentioning
confidence: 99%
“…Other clinical studies have demonstrated that high body iron stores are associated with decreased blood lead levels (Graziano et al 1990). These previous studies formed the basis of our hypothesis that the HFE gene would be a candidate gene for modifying lead absorption and body burden.…”
Section: )mentioning
confidence: 99%
“…17 The source of lead in the infant's blood seems to be a mixture of approximately two thirds dietary and one third skeletal lead, as shown by studies that exploited the differences in lead isotopes stored in the bones of women migrating from Europe to Australia. 18 Although lead appears in human milk, the concentration is closer to plasma lead and much lower than blood lead, so little is transferred.…”
Section: Transplacental Exposure and Lead In Human Milkmentioning
confidence: 99%
“…Based on the mean BPb levels of severely lead-poisoned Haina children and those of pregnant women from earlier and present groups, recent newborns in the community are expected to have high BPb levels and should be further investigated. Studies from similar situations have shown persistent high BPb levels in both mothers and newborns (35). This issue should be of equal or perhaps greater concern to the local public health authorities because the detrimental effect of lead causes far more severe damage in fetuses and newborns than in children or adults.…”
mentioning
confidence: 98%